Protocol for the Micropropagation of Coconut from Plumule Explants - Sáenz, Luis; Chan, José Luis; Narvaez, María; Oropeza, Carlos (Methods in molecular biology (Clifton, N.J.), 2018)
Coconut is a crop that is economically important in several countries throughout the world. Unfortunately, production is decreasing because palms are affected by very serious phytoplasma diseases, such as lethal yellowing, and also most of coconuts are already very old. On the other hand, markets for coconut products have been rapidly growing in recent years. Hence, replanting of most cultivation surface worldwide, as well as establishing new surface, is urgently needed. This is an immense task, requiring at least a billion coconut palms that cannot be accomplished by traditional propagation through seed. Therefore the biotechnological alternative of micropropagation by somatic embryogenesis is needed. Research has been carried out on this subject in laboratories in several countries studying different approaches, testing different types of explants. The most responsive tissue has been plumule from zygotic embryos. A protocol for micropropagation of coconut based on plumule explants is described here. It involves the use of different media that are based on Y3 medium complemented with activated charcoal, gelling agent, sucrose, and growth regulators. These media allow the formation of embryogenic callus and somatic embryos, growth of shoots, and development of plantlets.